A Survey of Malaysian Experience in TQM (Malaysian Management Journal, 2001)
This study documents the experience of Malaysian firms in the implementation of TQM. Issues being explored and documented are years required to fully implement TQM, benefits of TQM, the different kinds of TQM training conducted, and reasons for not adopting TQM. This paper also shows that adoption of TQM leads to improvement in organizational performance, and that the involvement of employees and senior executives is important to support TQM execution, irrespective of a firm' s paid-up capital and years of operation.